THE ANALYSIS OF ECONOMIC EFFICIENCY OF RED CHILLI BUSINESS IN SAWANG SUBDISTRICT, ACEH UTARA: English - Adhiana, Adhiana; Martina; Riani; Suryadi (CV. Radja Publika, 2021)
Red chili is one of the horticultural commodities that are needed by the community. However, the productivity of red chili in Aceh Utara is still low at 6.19 tons/ha. This study aims to analyze the factors that affect the production of red chili and analyze the economic efficiency of red chili farming in Sawang Sub-District, Aceh Utara. This research is located in Aceh Utara, precisely in Sawang Sub-District. The sampling method was carried out by census, namely as many as 40 red chili farmers. This study uses a data analysis method, namely the Cobb-Douglas function model with a Stochastic frontier approach. The results of the analysis show that the production factors that affect the production of red chili in Sawang District are land area, labor, and fertilizer, while the seed and pesticide production factors did not affect the red chili production. The results of the study also explained that red chili farming in the research location was technically efficient (ET=0.796), but did not achieve allocative and economical efficiency with the respective averages (EA = 0.439 and EE = 0.351).